Terlipressin therapy for moderate‐to‐severe hyponatraemia in patients with liver failure. Issue 3 (27th February 2013) - Prakoso, E.; Jones, C.; Koorey, D. J.; Strasser, S. I.; Bowen, D.; McCaughan, G. W.; Shackel, N. A.
Abstract Background Hyponatraemia in liver failure is associated with increased morbidity and mortality. Improving serum sodium in liver failure has been observed in patients receiving terlipressin. Methods We assessed the response of hyponatraemia in patients with liver failure to terlipressin using comparative retrospective analysis. Results Twenty‐three patients received terlipressin for hyponatraemia after failed conservative management (median age 52 years (27–67), model for end‐stage liver disease score 28 (16–38)). The median therapy was 7 days (1–27), with an average total dose of 25 mg (4–90) and a mean follow up of 51 days (5–1248). These patients were compared with 11 hyponatraemic patients managed conservatively during the same period with comparable age, baseline serum sodium and follow up. After 1 week of terlipressin therapy, serum sodium increased from a median of 120 (115–128) to 129 mmol/L (121–144) (P < 0.001), and at the end of terlipressin therapy, the serum sodium had increased significantly to 131 mmol/L (120–148) (P < 0.001). In comparison, in the conservatively managed group, the serum sodium did not increase significantly from the baseline of 123 (117–127) mmol/L. Adverse events occurred in 26% of patients receiving terlipressin, which predominantly pulmonary oedema. Importantly, more hyponatraemic patients treated with terlipressin (48%) were alive compared with the conservative group (18%), despite the latter having a significantly lower baseline median MELD score of 21 (16–30) (P = 0.008). Moreover, the transplant‐free survival was higher in the terlipressin (30%) compared with the conservative group (0%). Conclusions Terlipressin is effective in treating hyponatraemia in liver failure. Importantly, terlipressin use results in better transplant‐free survival but also more adverse events.